Literature Review Efektivitas Model Pembelajaran Berbasis Proyek (PjBL) untuk Meningkatkan Pemahaman Konsep Matematis Siswa SMA - Dini Amalia; Aan Hendrayana (De Fermat : Jurnal Pendidikan Matematika, 2026)
The low level of mathematical conceptual understanding among senior high school students remains an important issue in mathematics learning that affects students learning outcomes. This study aims to examine and evaluate the effectiveness of project based learning in improving the mathematical conceptual understanding of senior high school students. The study employed a systematic literature review method through the stages of identification, selection, eligibility assessment, and article analysis based on predetermined inclusion criteria. The articles were collected from Google Scholar and Science and Technology Index databases within the publication period of 2020 to 2025. Based on the selection process, 4 empirical articles met the criteria and were further analyzed. The findings showed that project based learning consistently improved students mathematical conceptual understanding as indicated by the improvement in learning outcomes and learning gain scores within moderate to high categories. In addition, active student participation and the use of appropriate instructional media also supported the effectiveness of learning in helping students understand mathematical concepts more deeply. Therefore, project based learning is effective to be implemented in improving the mathematical conceptual understanding of senior high school students.